Menghadapi Rasa Takut Tertinggal: Fenomena Fear Of Missing Out (Fomo) Di Kalangan Mahasiswa - Rahma Indah Kusumaningrum; Ayundha Sintya Setyaningtyas; Rauly Sijabat (JURNAL ILMIAH NUSANTARA, 2026)
The rapid development of digital technology and social media has significantly transformed social interaction patterns among university students. One psychological phenomenon that emerges from this condition is Fear of Missing Out (FOMO), defined as the anxiety arising from the fear of missing valuable experiences or information experienced by others. This phenomenon becomes increasingly prominent due to the intensive use of social media platforms among students. This study aims to explore how students perceive the experience of FOMO, identify contributing factors, and understand the strategies they use to cope with it. This research employs a qualitative phenomenological approach. Data were collected through in-depth interviews, observations, and documentation involving active university students who frequently use social media. The findings reveal that FOMO is driven by the need for social connectedness, social comparison in digital environments, and dependence on social media. FOMO affects students’ emotional well-being, academic focus, and psychological health. However, some students have begun to develop coping strategies, such as regulating social media usage and enhancing self-awareness. This study concludes that FOMO is a complex psychosocial phenomenon that requires attention in efforts to maintain students’ mental health in the digital era.